Newborn follow-up after discharge from a tertiary care hospital in the Western Cape region of South Africa: a prospective observational cohort study - Jean Paul Muambangu Milambo; KaWing Cho; Charles Okwundu; Abiola Olowoyeye; Leonidas Ndayisaba; Sanjay Chand; Mark H. Corden (BMC, 2018)
Abstract Background Current practice in the Western Cape region of South Africa is to discharge newborns born in-hospital within 24 h following uncomplicated vaginal delivery and two days after caesarean section. Mothers are instructed to bring their newborn to a clinic after discharge for a health assessment. We sought to determine the rate of newborn follow-up visits and the potential barriers to timely follow-up. Methods Mother-newborn dyads at Tygerberg Hospital in Cape Town, South Africa were enrolled from November 2014 to April 2015. Demographic data were obtained via questionnaire and medical records. Mothers were contacted one week after discharge to determine if they had brought their newborns for a follow-up visit, and if not, the barriers to follow-up. Factors associated with follow-up were analyzed using logistic regression. Results Of 972 newborns, 794 (82%) were seen at a clinic for a follow-up visit within one week of discharge. Mothers with a higher education level or whose newborns were less than 37 weeks were more likely to follow up. The follow-up rate did not differ based on hospital length of stay. Main reported barriers to follow-up included maternal illness, lack of money for transportation, and mother felt follow-up was unnecessary because newborn was healthy. Conclusions Nearly 4 in 5 newborns were seen at a clinic within one week after hospital discharge, in keeping with local practice guidelines. Further research on the outcomes of this population and those who fail to follow up is needed to determine the impact of postnatal healthcare policy.